THE INFLUENCE OF DIGITAL MARKETING CONTENT ON THE PURCHASE DECISION (STUDY ON ERIGO PRODUCT USERS IN SEMARANG CITY) - Zahrani, Salma Fadhiila; Marlien, R.A (STIE Pelita Nusantara Semarang, 2023)
As a well-known local clothing brand, Erigo has its own online marketing method to increase product sales in order to attract a large number of consumers. This study aims to analyze the influence of Content Marketing, Influencer Marketing and Online Customer Reviews on Purchase Decisions on Erigo products. The research population is consumers who have purchased clothing products from Erigo, which were taken from 110 respondents who live in the city of Semarang and used a purposive sampling research method. The results of the study state that influencer marketing and online customer reviews have an influence on purchasing decisions, in contrast to content marketing which does not have an influence on purchasing decisions. Simultaneously content marketing, influencer marketing and online customer reviews have an influence on purchasing decisions.